Evaluasi Perbandingan Sistem Rantai Dingin Penyimpanan Vaksin - Maelana Eka Dewi; Iswandi Iswandi; meta kartika (Journal Syifa Sciences and Clinical Research, 2022)
Vaccines are preparations of biological products that contain antigens or contain components of microorganisms that have been attenuated from genetic engineering. Defective vaccine quality can be caused by the time of the cold chain storage process that is not in procedure. This study aims to compare the vaccine cold chain system in the warehouse of the City Health Office and Salatiga City Health Center which is guided by the Indonesian Minister of Health Regulation Number 12 of 2017. This type of research uses a descriptive observational method. The data collected in the form of quantitative and qualitative. Collecting qualitative data obtained from interviews and observations. Qualitative data were obtained from vaccine storage data in 2021. The results of the study obtained that he cold chain compatibility system at the City Health Office and Salatiga City Health Center was in good category, with the percentage of the City Health Office 88.88%, Cebongan Health Center 77.77%, Mangunsari Health Center 70.37%, Kalicacing Health Center 85.18%, Tegalrejo Health Center 81.48%, Sidorejo Lor Health Center 81.48%, Sidorejo Kidul Health Center 77.77%. Supporting facilities for vaccine storage are in accordance with the guidelines of the Permenkes RI Nomor 12 tahun 2017, in good category. With the percentage of the City Health Office 99.64%, Cebongan Health Center 96.87%, Mangunsari Health Center 97.02%, Kalicacing Health Center 91.80%, Tegalrejo Health Center 94.11%, Sidorejo Lor Health Center 96.29%, Sidorejo Kidul Health Center 98,30%.